Neospora caninum NC-6 Argentina induces fetopathy in both serologically positive and negative experimentally inoculated pregnant dams - Bacigalupe, Diana; Basso, W.; Caspe, Sergio Gaston; More, Gastón; Lischinsky, Lilian Haydee; Gos, María Laura; Leunda, Maria Rosa; Campero, Lucía María; Moore, Prando Dadin; Schares, Gereon; Campero, Carlos Manuel; Venturini, María Cecilia (2018)
Neospora caninum infection is a major cause of abortion in cattle. The objectives of this study were to genetically characterize the N. caninum NC-6 Argentina isolate using a multilocus microsatellite analysis approach and to study its biological behavior by experimental inoculations into seronegative and seropositive pregnant cattle, evaluating the humoral and cellular immune response elicited and the occurrence of transplacental transmission and fetopathy. Pregnant cows (65 days of gestation) seropositive and seronegative to N. caninum were intravenously inoculated with tachyzoites of the NC-6 Argentina N. caninum strain and slaughtered at 108 ± 2 days of gestation. Serum samples were analyzed for N. caninum antibodies by indirect fluorescent antibody test. The cellular immune response was analyzed by detection of gamma interferon (γIFN) production in blood cells. Tissue samples from dams, fetuses, and placental cotyledons were processed by histopathological and immunohistochemical techniques and examined for N. caninum DNA by PCR. Positive DNA samples were further analyzed by multilocus microsatellite typing for N. caninum. Inoculated animals had significantly higher N. caninum antibody titers and γIFN production than control animals. One seropositive inoculated cow aborted, one seronegative cow had a non-viable fetus, and the remaining fetuses from the experimentally inoculated dams had histopathologic lesions. The PCR was positive in 3/4 fetuses from seronegative inoculated cows and in 2/3 fetuses from seropositive inoculated cows. Multilocus microsatellite analysis revealed that the N. caninum DNA present in fetuses and placentas had an identical pattern to NC-6 Argentina strain. The NC-6 Argentina strain proved to be able to cross the placenta and to induce fetopathy in both the seropositive and seronegative dams.